PERBURUAN SATWA LIAR DI DESA SINSINGON KECAMATAN PASSI TIMUR - Astria Retrisna Werung; Johny S. Tasirin; Martina A. Langi (Universitas Sam Ratulangi, 2020)
Humans use wildlife in various ways and often cause a decline inendangered populations (Alikodra, 2010). The increasing number of humanpopulation has an impact on the expansion of development in various sectorsincluding opening of forest areas for plantations and mining, This study aims todetermine the poaching of wild animals in Sinsingon Village, East Passi District.The results of the study there are 8 types of wild animals being labored, namelyRats (Rattus sp) 100%, Wild Boar (Sus celebensis) 30.4%, Kus-Kus (Ailuropsursinus) 30.4%, Bats (Chairoptera) 21.7%, Mandars (Gallirallus philippensis)21.7%, Pergamos (Gallirallus philippensis) 13.0%, Yaki (Macaca Nigra) 8.7%,Snakes (Python reticulatus) 4.3% .Keywords: Wildlife, poaching of Wildlife